A new procedure for autonomous acquisition of photosynthesis-irradiance curves on a microphytobenthic biofilm - Meresse, Marvin; Gevaert, François; Duong, Gwendoline; Denis, Lionel (Frontiers in Marine Science, 2023)
Despite their high productivity and their key role in coastal processes, microphytobenthic biofilm studies remain relatively scarce because in situ, meteorological hazards make it difficult to acquire reproducible measurements, also due to difficulties in properly reproducing field conditions in the laboratory. Therefore, in order to better understand the processes of microphytobenthic primary production, we have developed an automated laboratory system and procedure with variable light intensity, with a large number of replicates. This article aims to provide a description of the creation of a P-I curve based on a total of 128 vertical profiles recorded on a sediment core taken in situ, placed in the automated system and studied under controlled conditions of temperature and air humidity while light intensity was varied automatically, thus allowing to work in standard and replicable conditions. With measured production levels of up to 14.68 ± 3.70 mmol O2.m-2.h-1 and a productivity of 0.06 ± 0.01 mmol O2.m-2.h-1 per gram of Chl a corresponding to what is generally found in temperate environments, we have shown that our system is suitable for high frequency measurements and, by combining surficial measurements of modulated fluorescence and oxygen microprofiling in sediments, complementary information from a large dataset on photosynthetic and microphytobenthic migratory activity may be obtained under standard conditions. The development of this tool has made it possible to highlight a stabilization time for oxygen fluxes. For our study conducted in a temperate environment, we observed a time lag of a few minutes that should be considered when acquiring PE curves in the laboratory to study microphytobenthic photosynthetic capacities. This tool also allowed to describe microphytobenthic migration in response to light exposure, with successive steps observed through fluorescence and oxygen profiles. First, microphytobenthos migrated towards the surface until the optimal intensity of production at 475 µmol photons.m-2.s-1, then from this intensity as well as towards 780 µmol photons.m-2.s-1, downwards migratory movements were detected. This system is a working basis which can open interesting perspectives for the study of the effect of other abiotic (or biotic) parameters.